2023
DOI: 10.3389/fonc.2022.1025284
|View full text |Cite
|
Sign up to set email alerts
|

A clinical prognostic model for patients with esophageal squamous cell carcinoma based on circulating tumor DNA mutation features

Abstract: BackgroundFew predictive models have included circulating tumor DNA (ctDNA) indicators to predict prognosis of esophageal squamous cell carcinoma (ESCC) patients. Here, we aimed to explore whether ctDNA can be used as a predictive biomarker in nomogram models to predict the prognosis of patients with ESCC.MethodsWe included 57 patients who underwent surgery and completed a 5-year follow-up. With next-generation sequencing, a 61-gene panel was used to evaluate plasma cell-free DNA and white blood cell genomic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 32 examined GEA. Of these, five studies targeted Western populations 22 , 24 , 27 , 31 , 32 , while the remaining eight focused on Asian populations 23 , 25 , 26 , 28 30 . Among the aforementioned investigations, seven were characterized as prospective population studies, and six were identified as retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 examined GEA. Of these, five studies targeted Western populations 22 , 24 , 27 , 31 , 32 , while the remaining eight focused on Asian populations 23 , 25 , 26 , 28 30 . Among the aforementioned investigations, seven were characterized as prospective population studies, and six were identified as retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma DNA extraction was performed in all studies for subsequent measurement. Several methods were applied in the examination of ctDNA among the studies: (1) next-generation sequencing (NGS) gene panels 22 , 23 , 25 28 , 30 , 32 , (2) digital polymerase chain reaction (dPCR) 29 , 30 , (3) droplet digital polymerase chain reaction (ddPCR) 24 , 32 . The clinical endpoint in nearly 77% of the studies (10/13) was OS, followed by PFS in 6/13 studies and DFS/RFS in 4/13 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation